2012
DOI: 10.3758/s13414-012-0384-y
|View full text |Cite
|
Sign up to set email alerts
|

Sources of bias and uncertainty in a visual temporal individuation task

Abstract: Despite a clear ability to detect temporal modulations of visual stimuli in excess of 50 Hz, temporal individuation and serial order judgment tasks can be performed only when stimuli alternate at much slower rates, and the nature of such sluggishness remains unclear. One example of a task with a slow temporal limit is the individuation of a cued letter in a rapid serial visual presentation (RSVP) stream. The present study investigates the nature of the code used to perform such a slow temporal individuation ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 60 publications
5
16
0
Order By: Relevance
“…The result seems consistent with previous suggestions that training improves T2 reports owing to increased attentional control (Choi et al, 2012). It is also consistent with the notion that training improves temporal expectation (Tang et al, 2014; Willems et al, 2014), in as much as temporal expectation improves efficacy of selection, as reported by Martini (2013).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The result seems consistent with previous suggestions that training improves T2 reports owing to increased attentional control (Choi et al, 2012). It is also consistent with the notion that training improves temporal expectation (Tang et al, 2014; Willems et al, 2014), in as much as temporal expectation improves efficacy of selection, as reported by Martini (2013).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we computed efficacy, latency and precision of selection using a method similar to that used by Vul, Nieuwenstein, and Kanwisher (2008) and Martini (2013). The method is based on the analysis of serial position error of the reported letters at different lags.…”
Section: Methodsmentioning
confidence: 99%
“…Processing of the first target in attentional blink tasks may be limited by the temporal imprecision of attentional selection, but unfortunately it is rarely studied. The evidence available is that the precision of selection of the first target in a rapid serial visual presentation (RSVP) stream (Martini, 2012;Vul, Nieuwenstein, & Kanwisher, 2008) has a standard deviation of approximately 70 ms. Approximately the same figure is found for judging the instantaneous position of a moving object at the time of a cue (Murakami, 2001;Linares, Holcombe, & White, 2009).…”
Section: Temporal Resolution Of High-level Visionmentioning
confidence: 99%
“…One might expect that the appearance of the cues would trigger sampling from the stream, resulting in the reported letters being either simultaneous with the cue or from some time after the cue-a positively skewed distribution of serial-position errors. Instead, the distribution of positions is symmetric, with many coming from before the time of the cue (Botella, Suero, & Barriopedro, 2001;G&H;Martini, 2013). Based on these findings, G&H theorized that even the letters presented before the cue activate orthographic representations, that the activation of these representations persists, and that subsequently the cue is bound to one of them (for a related model that anticipates some of these ideas, see Botella, Suero, & Barriopedro, 2001).…”
Section: Simultaneous Selection But Prioritized Processingmentioning
confidence: 99%